Accuracy of behavioral health variables in Oregon national violent death reporting system data: a linked cohort study - Kathleen F. Carlson; Tess A. Gilbert; Susan DeFrancesco; Dagan A. Wright; Xun Shen; Lawrence J. Cook (BMC, 2022)
Abstract Background The National Violent Death Reporting System (NVDRS) collects data on the circumstances of violent deaths, and all firearm-related deaths, across states and territories in the USA. This surveillance system is critical to understanding patterns and risk factors for these fatalities, thereby informing targets for prevention. NVDRS variables include behavioral health conditions among decedents, but the validity of the reported behavioral health data is unknown. Using Department of Veterans Affairs (VA) healthcare records as a criterion standard, we examined the accuracy of NVDRS-reported behavioral health variables for veteran decedents in a sample state (Oregon) between 2003 and 2017. Methods We linked Oregon NVDRS data to VA healthcare data to identify veteran decedents who used VA services within two years of death. Veterans' VA diagnoses within this time frame, including depression, post-traumatic stress disorder (PTSD), anxiety, and substance use disorders, were compared to behavioral health variables identified in the Oregon NVDRS. Concordance, sensitivity, and correlates of sensitivity were examined over time and by decedent characteristics. Results We identified 791 VA-using veterans with violent and/or firearm-related fatal injuries documented in the Oregon NVDRS between 2003 and 2017. In this cohort, the Oregon NVDRS accurately identified only 49% of decedents who were diagnosed with depression, 45% of those diagnosed with PTSD, and 17% of those diagnosed with anxiety by the VA. Among 211 veterans diagnosed by the VA with a substance use disorder, the Oregon NVDRS coded only 56% as having a substance use problem. In general, the sensitivity of behavioral health variables in the Oregon NVDRS remained the same or decreased over the study period; however, the sensitivity of PTSD diagnoses increased from 21% in 2003-2005 to 54% in 2015-2017. Sensitivity varied by some decedent characteristics, but not consistently across behavioral health variables. Conclusions NVDRS data from one state missed more than half of behavioral health diagnoses among VA-using veterans who died from violence or from firearm injuries. This suggests that reports of behavioral health conditions among decedents nationally may be severely undercounted. Efforts to improve validity of these variables in state NVDRS data are needed.